PO.6.120 Non-pharmacological management of systemic lupus erythematosus and systemic sclerosis: a systematic literature review to inform eular recommendations. (27th September 2022) - Parodis, I; Gomez, A; Tsoi, A; Chow, JW; Pezzella, D; Girard, C; Stamm, T; Boström, C
Abstract : Purpose: The heterogeneity and complexity of the chronic autoimmune diseases systemic lupus erythematosus (SLE) and systemic sclerosis (SSc) necessitate a comprehensive person-centred management, including non-pharmacological approaches. However, recommendations for non-pharmacological management are currently lacking. The aim of this systematic literature review was to inform the EULAR task force recommendations for the non-pharmacological management of adult patients with SLE and SSc, focusing on (i) types of non-pharmacological interventions that have been evaluated and (ii) their target health domains or organ systems. Methods: The Medline, Embase, Web of Science Core Collection and CINAHL were searched for articles published between January 2000 and June 2021. From the initial search (n=15, 803), 2 researchers independently performed the article selection. Conflicts were discussed until consensus with 2 additional researchers. Subsequent data extraction from the selected articles was performed by 4 researchers, with an overarching guidance by 2 additional researchers. Risk of bias assessment was performed according to the Joanna Briggs Institute critical appraisal checklists (presented in the table below). Results: A total of 114 articles for SLE and 92 for SSc were selected for analysis. Non-pharmacological interventions identified for SLE included physical exercise (n=34), psychological interventions (n=21), patient education and self-management (n=20), dietary therapy and nutrition (n=15), complementary and alternative medicine (CAM) e.g., Chinese medicine (n=5), photoprotection (n=5), health care (n=4), laser treatment (n=4) and social support (n=2). Interventions identified for SSc included physical exercise e.g., hand, oral and general exercise (n=37), laser treatment/phototherapy (n=11), patient education and self-management (n=11), CAM (n=10), bathing e.g., hand-bathing in paraffin (n=9), manual therapy e.g., osteopathic manipulative treatment (n=8), dietary therapy and nutrition (n=6), shockwave therapy (n=5), multidisciplinary care (n=4), hyperbaric oxygen or ozone therapy (n=3) and oral hygiene (n=3). Target health domains and organ systems identified within SLE included (in descending order) (i) health-related quality of life (HRQoL), (ii) disease activity, (iii) fatigue, (iv) depression, (v) inflammatory markers, (vi) pain, (vii) anxiety, (viii) organ damage, (ix) body composition/anthropometry, and (x) self-efficacy. Intervention targets in SSc included (i) functional impairment e.g., hand mobility, (ii) skin sclerosis including microstomia, (iii) HRQoL, (iv) pain, (v) circulation e.g., Raynaud's phenomena and telangiectasias, (vi) patient education, (vii) skin ulcers, (viii) biomarkers, (ix) digestion, and (x) oral hygiene. Conclusions: Physical exercise and patient education were among the most extensively studied categories of non-pharmacological intervention in both SLE and SSc. HRQoL was a frequently targeted health domain in both diseases. Current evidence is limited by the overall small study populations, and the lack of large RCTs with long-term follow-up periods.